PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUTOPLAY MEDIA STUDIO 8.5.2.0 PADA MATA PELAJARAN IKATAN KIMIA UNTUK SISWA KELAS X MADRASAH ALIYAH NEGERI 1 KUANTAN SINGINGI - Banyas Ambara; Asregi Asril; Dwi Putri Musdansi (Universitas Islam Kuantan Singingi, 2020)
Research on the development of interactive learning media based on Autoplay Media Studio 8.5.2.0 aims to explain the feasibility of developing interactive based Autoplay Media Studio 8.5.2.0 in chemical bonding subjects for X Grade Student of State Islamic Senior High School 1 Kuantan Singingi. This research method is research and development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Data collection instruments used were through expert material validation sheets, learning media validation sheets, and student response validation sheets. The data analysis technique used is by calculating the validation assessment percentage score. The results showed that the interactive learning media based on Autoplay Media Studio 8.5.2.0 that was developed fulfilled the valid categories of material experts in the amount of 91.16% and in the media experts amounted to 94.58%. This learning media also fulfills a valid category which students can use with 96.25%.